A specular microscopic study of families with endothelial dystrophy. Issue 6 (June 1981) - Schnitzer, J I; Krachmer, J H
Abstract : A prospective study of 12 families in which the proband had Fuchs's dystrophy was undertaken. Forty-four relatives were examined with the clinical specular microscope. Nine relatives, all women over 40 years of age, were affected. The mean endothelial cell density for unaffected relatives was 2889 cells/mm2 in the right eye and 2923 cells/mm2 in the left eye. Variability in endothelial cell size was not present in unaffected relatives but was present in those relatives with cornea guttata. Endothelial cell density decreased with age. The mean corneal thickness for unaffected and affected relatives was 0.51 mm and 0.53 mm, respectively. Unaffected relatives were compared with a control group with respect to endothelial cell density and corneal thickness. No significant difference was found between the 2 groups. In this study the clinical specular microscope failed to differentiate between controls and relatives of patients with Fuchs's dystrophy who at the time of examination did not have endothelial dystrophy. The instrument, therefore, could not be used to identify endothelial characteristics not visible with the slit-lamp which might be the forerunner of endothelial dystrophy.